Auxotrophy accounts for nodulation defect of most Sinorhizobium meliloti mutants in the branched-chain amino acid biosynthesis pathway - Peltzer, María de las Nieves (2008)
Some Sinorhizobium meliloti mutants in genes involved in isoleucine, valine, and leucine biosynthesis were previously described as being unable to induce nodule formation on host plants. Here, we present a reappraisal of the interconnection between the branched-chain amino acid biosynthesis pathway and the nodulation process in S. meliloti. We characterized the symbiotic phenotype of seven mutants that are auxotrophic for isoleucine, valine, or leucine in two closely related S. meliloti strains, 1021 and 2011. We showed that all mutants were similarly impaired for nodulation and infection of the Medicago sativa host plant. In most cases, the nodulation phenotype was fully restored by the addition of the missing amino acids to the plant growth medium. This strongly suggests that auxotrophy is the cause of the nodulation defect of these mutants. However, we confirmed previous findings that ilvC and ilvD2 mutants in the S. meliloti 1021 genetic background could not be restored to nodulation by supplementation with exogenous amino acids even though their Nod factor production appeared to be normal.